Knowledge, views and attitudes regarding the internet and its use in dentistry among dental undergraduate and postgraduate students -an obsrvational study - PRABHU, Namdeo; RAKHI, Issrani (International Arab Journal of Dentistry (IAJD), 2016)
The use of computer and information technology is on escalation. There is little contemporary literature outlining the knowledge, views and attitudes of dental students regarding the use of the internet in dentistry especially in our country, India. Hence, it was decided to conduct a pilot questionnaire study regarding the internet and its use in dentistry among dental undergraduate (UG) and postgraduate (PG) students. A prospective, cross-sectional, self-designed questionnaire with questions on various aspects of usage of the internet by the dental students was circulated among the UG and PG students at two dental institutes of Belgaum, Karnataka, India: KLE VK Institute of Dental Sciences (KLE VKIDS) and Maratha Mandal’s NGH Institute of Dental Sciences and Research Centre (MMDC). Completed questionnaires were received from 284 out of 335 UG students and 112 out of 196 PG students, with a response rate of 84.8% and 57.14%, respectively. 82.04% of UG and 87.5% of PG students had personal laptops with access to the internet, indicating easy accessibility to technology. E-mail/surfing was the most common purpose of the internet usage among all the students. tient relationship. Our study highlights that the internet technology is regularly used for entertainment than for academic purposes. Hence each graduating dentist should not only have a thorough knowledge of the internet but should also be trained for literature search and this can only be accomplished by proper and compulsory trai- ning of these students for various applications of the internet in dentistry as practicing evidence-based health care might come in huge way tomorrow.